: English - Oktifani Winarti (Jurnal Spektrum Komunikasi, 2023)
Study shows the meaning of laughter can be varied. This article is discussing about the meaning of laughter between a mother and her daughter in the context of health communication, especially within an end-stage disease namely Cystic Fibrosis. This article is using a Conversation Analysis as a method to analyse a series of interaction and divided into several parts of conversation excerpts. The previous studies have also consistently demonstrated that laughter has positive effects on human interaction and social behaviour, including increased social connection, improved mood, and enhanced coping, especially within a ‘crisis moment’ such as coping with an end-stage diseases. This study breaks down the interaction that shows how frustrating life events can be a laugh-worthy memories.